Effects of high pressure on electrochemical processes. - Currie, John Carleton. (University of Ottawa (Canada), 1977)
The significance of effects of pressure on the kinetics and equilibria of chemical processes in the condensed phase has been known since the time of van't Hoff. The use of pressure as an extra variable has become an integral part of kinetic and related studies on reactions over the past 25 years. However, interest in the behaviour of electrochemical processes as a function of pressure is of more recent origin (<10 years); consequently, experimental data are relatively scarce. This thesis describes the pressure dependent behaviour of a variety of electrochemical reactions of fundamental and practical interest. The pressure coefficient of EMF of several electrochemical cells comprised of two reversible electrodes is evaluated in order to determine their suitability for use as reference electrodes at elevated pressures. The electrochemical cells examined are: (1) Pt,H2|0.5 M H2SO4 |Pd-H,Pd; (2) Pt,H2|1.0 M HCl|Pd-H,Pd and (3) Pd,Pd-H|HCl|AgCl,Ag. The pressure coefficient of EMF of each electrode cell is converted to the partial molar volume change for the corresponding overall cell reaction. The partial molar volumes of Pd-H,H in Pd and of H2 itself in solution are also evaluated. The reproducibility of the measured pressure coefficients indicates that the Ag,AgCl and Pd-H,H+ reference electrodes are the most suitable of those evaluated for use at elevated pressures. The effects of high hydraulic pressures on the kinetics of electrode reactions are complex because of (a) the variation of reference electrode potentials with pressure so that only an apparent volume of activation can be directly measured experimentally and (b) dependence of coverage by adsorbed intermediates, such as H, with pressure. Methods for dealing with these problems are treated and the significance of measured apparent volumes of activation for the hydrogen evolution reaction is discussed in terms of the nature of the transition state for proton transfer and neutralization. The negative true volumes of activation found for the cathodic H2 evolution reaction under some conditions are attributed to increasing electrostriction of the proton in the H9O+4 complex as the transition state is formed. New information on the nature of the solvent reorganization process involved in formation of the transition state in an electrochemical redox reaction [the Fe&parl0;CN&parr0;3-6/Fe&parl0;CN&parr0; 4-6 couple] is given by studies of the kinetics of this process at high pressures in aqueous solutions at Au. The apparent activation volume is evaluated together with the true volumes of activation for the forward and reverse directions of the redox reaction. By means of calculations of the electrostriction associated with the long-range dielectric polarization in comparison with that associated with ion-solvent interaction in the primary hydration shell, it is shown that the activation process must be mainly (75%) due to short-range solvent reorganization in the primary shell. This is contrary to what has often been assumed in the interpretation of the energy of activation of ionic redox reactions. The experiments also allow some deduction to be made about the "symmetry" of the transition states in electrochemical reactions in comparison with that in the corresponding homogeneous reactions, in so far as solvent reorganization is concerned. The multiple states of electrosorbed H and oxygen species at Pt, which arise below monolayer coverage, are of current interest in electrochemical surface science. Experiments on the effects of high hydraulic pressure on H chemisorption and surface oxide formation at Pt electrodes are described. "Clean" electrochemical surface studies can be performed in a shrinkable teflon vessel, under oil, up to several thousand bars. The results of these experiments enable the equilibrium volume changes for electrodeposition of H and surface oxidation of Pt to be evaluated, allowing for the effect of pressure on the potential of the reversible reference electrode used. The volume of electrodeposited H is found to be ca. 5 cm3mol -1 at Pt, a value substantially larger than that for sorption of H into (alpha + beta) Pd-H but similar to that of H covalently bound in aliphatic hydrocarbon methylene groups. (Abstract shortened by UMI.)
Keywords: Chemistry, Analytical.